2019
DOI: 10.1111/febs.14734
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen triggers signal transduction in the DevS (DosS) sensor of Mycobacterium tuberculosis by modulating the quaternary structure

Abstract: A major challenge to the control and eventual eradication of Mycobacterium tuberculosis infection is this pathogen's prolonged dormancy. The heme‐based oxygen sensor protein DevS (DosS) plays a key role in this phenomenon, because it is a major activator of the transcription factor DevR. When DevS is active, its histidine protein kinase region is ON and it phosphorylates and activates DevR, which can induce the transcription of the dormancy regulon genes. Here, we have investigated the mechanism by which the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 78 publications
(109 reference statements)
1
10
0
Order By: Relevance
“…These studies provide support for the actual responses to the ligands on the HD in a context of a full-length protein, which has showed to be quite distinct [36]. Indeed, more recently, we showed, depending on the ligand bound to DevS, oligomerization can be altered, where octamers are mainly found in the active states while tetramers and dimers in the inactive states [40]. Despite these major changes, our electrochemistry results did not provide any clear disturbance on the measurements.…”
Section: 92supporting
confidence: 67%
See 1 more Smart Citation
“…These studies provide support for the actual responses to the ligands on the HD in a context of a full-length protein, which has showed to be quite distinct [36]. Indeed, more recently, we showed, depending on the ligand bound to DevS, oligomerization can be altered, where octamers are mainly found in the active states while tetramers and dimers in the inactive states [40]. Despite these major changes, our electrochemistry results did not provide any clear disturbance on the measurements.…”
Section: 92supporting
confidence: 67%
“…) present structural evidence that might explain the differences in the redox behaviors of such proteins regarding ligand binding. Unfortunately, there is not much study on the full‐length conformational changes associated with signal transduction for DevS or DevS/DevR , whereas only one detailed structural study for full‐length FixL has been published .…”
Section: Discussionmentioning
confidence: 99%
“…There are three ppk genes encoding PPK in the NM-1 strain, and these genes are responsible for the synthesis of poly-P from ATP (He and McMahon, 2011; Kawakoshi et al, 2012). According to our results with RT-qPCR (Lobao et al, 2019), genes related to the biosynthesis of poly-P, including ppk (MLP_RS23025) and ppk2 (MLP_RS24205), were significantly down-regulated under anaerobic conditions, while the transcription level of ppk2 (MLP_RS02760) showed no obvious changes under aerobic or anaerobic conditions (Figure 4B). PPNK (MLP_RS08475), PAP (MLP_RS11265), PPX (MLP_RS21635), and PPGK (MLP_RS02595, MLP_RS12905) are the enzymes that catalyze poly-P into NADP, ADP, Pi and glucose-6-phosphate, respectively (He and McMahon, 2011; Kawakoshi et al, 2012).…”
Section: Discussionmentioning
confidence: 54%
“…Although the metabolism of poly-P differed in NM-1 under aerobic and anaerobic conditions, the genes regulating the response to the changing levels of dissolved oxygen remained largely uncharacterized. In Mycobacterium tuberculosis , the DevS-DevR TCS responds to oxygen levels, with the GAF domain of the HK DevS sensing oxygen signals, and following phosphorylation by DevS, the RR DevR regulates the expression of dormancy-related genes (Madrona et al, 2016; Lobao et al, 2019). We speculated that a TCS might mediate the transition response to changing oxygen levels in M. phosphovorus , and bioinformatics analysis indicated that its genome (NC_015635.1) contained three genes encoding proteins with GAF-like domains: MLP_RS09510, MLP_RS09650, and MLP_RS10500 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation